Development Of A Pressure-Based Typing Biometrics System For User Authentication - Loy, Chen Change (Universiti Sains Malaysia, 2005)
Password authentication is the most prevalently used identification system in today’s cyber world. In spite of the popularity of this approach there are many inherent flaws. The password plays the role as the key to a lock; anyone who has it can gain successful access. Additionally, passwords can be easily cracked, guessed, stolen or deliberately shared. To minimize the risk of intrusion, keystroke dynamics can be used to complement this popular authentication method. As the name implies, it is an automated biometric method that analyzes the way a person types on a keyboard. There have been a lot of studies on using keystroke timing characteristics to verify the identity of a user. In this project keystroke pressure (the amount of force exerted on each key pressed) was employed, and its performance was compared with that of the conventional keystroke timings-based technique. The project also investigated the use of combined keystroke pressure and latency for the identification process. In order to measure the forces exerted during typing, a pressure-sensitive keyboard system was developed. A user interface that simulates actual login environment was used to collect data from 100 users. All users were requested to enter the same password. Three different classification methods were applied, namely Logistic Regression (LR), Multilayer Perceptron (MLP), and Fuzzy ARTMAP (FAM) neural networks. The results were very encouraging, with a maximum accuracy rate of 93.9% achieved by using FAM. Keystroke latency gave better results than keystroke pressure, but using both techniques together yielded the best results, with False Acceptance Rate (FAR) of 0.87% and False Rejection Rate (FRR) of 4.4%. The experimental results demonstrated that the proposed methods are promising, and that the keystroke pressure is a viable and practical way to add more security to conventional typing biometrics authentication system.